Amino acid digestibility and energy content of two different soy hull sources for swine - J Y Jacela; R C Sulabo; Joel M DeRouchey; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2007)
This trial was conducted to determine and compare the digestibility of amino acids and energy of soy hulls from two different sources. Five growing barrows (initially 150 lb) fitted with T-cannulas were each fed three different diets in a crossover design. Each of the first two diets contained 66.7% soy hulls from two different sources (Soy hulls A and Soy Hulls B). The third experimental diet was N-free and based on corn starch and sucrose for determining basal endogenous amino acid (AA) losses. Ileal digesta and fecal samples were collected during each period and analyzed for amino acid and energy contents. Due to poor flowability of digesta through the T-cannula of one pig when fed diets containing soy hulls, it was removed from the experiment and thus, only four pigs were used in all data analyses. Apparent (AID) and standardized (SID) ileal digestibilites, and gross (GE), digestible (DE), metabolizable (ME), and estimated net (NE) energy values were then calculated from these analyses. Both samples were analyzed for particle size using Ro-Tap shaker with a stack of Tyler screens. Particle size of soy hulls A and soy hulls B were 619 and 691Î¼, respectively. The results of the trial showed differences in nutrient composition and in amino acid and energy digestibilities between the two soy hulls. Apparent ileal digestibility values of lysine, methionine, and threonine in soy hulls A were 58.38, 65.93, and 50.68%, respectively and 51.10, 57.51, and 37.54%, respectively in soy hulls B. Standardized ileal digestibility values of the same amino acids were 61.13, 69.53, and 62.25%, respectively for soy hulls A and 54.60, 62.32, and 51.96%, respectively for soy Hulls B. As a percentage of CP, standardized ileal digestible lysine, methionine, and threonine values were 4.09, 0.83, and 2.16% for soy hulls A; and 4.01, 0.85, and 2.01% for soy hulls B, respectively. The ME, DE, and estimated NE values were 1,037; 1,097; and 722 kcal/lb for soy hulls A and 989, 1,030, and 680 kcal/lb for soy hulls B, respectively.; Swine Day, 2007, Kansas State University, Manhattan, KS, 2007
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-121-S; Swine day; 2007; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 985; Feed ingredients; Soy hulls; Digestibility; Swine